Dimensi Judicial Activism dalam Putusan Mahkamah Konstitusi - Faiz, Pan Mohamad (Jurnal Konstitusi, 2016)
A transformative amendment of the 1945 Constitution established a separate judicial institution called the Constitutional Court. This institution is believed to serve a strategic role within Indonesia’s plural legal  system  particularly  in  the area of constitutional review and constitutional rights protection. However, the performance of the Constitutional Court has attracted controversy. This controversy arises because the Court is concerned with introducing a sociological paradigm of law that embraces substantive justice with a fluid acknowledgment of procedural justice. A key criticism of the Constitutional Court is that the nature of Court decisions has developed into a practice of judicial activism. This article discusses the dimension of judicial activism used by the Constitutional Court on the grounds for protecting constitutional rights of the citizens through its decisions. It also analyses the extent of judicial activism that can be justified in the decision-making process   in the Constitutonal  Court.